To determine the x-intercepts of the translated function, we first need to figure out the new function after translating \( f(x) = x^2 \) down 4 units.
When we translate the function down 4 units, the new function becomes:
\[ f(x) = x^2 - 4 \]
Next, we find the x-intercepts by setting the function equal to zero:
\[ x^2 - 4 = 0 \]
Now, we can factor this equation:
\[ (x - 2)(x + 2) = 0 \]
Setting each factor to zero gives us the solutions:
\[ x - 2 = 0 \quad \Rightarrow \quad x = 2 \] \[ x + 2 = 0 \quad \Rightarrow \quad x = -2 \]
Thus, the x-intercepts of the function are:
\[ x = -2 \quad \text{and} \quad x = 2 \]
So the correct response is:
x = -2 and x = 2.